2020
DOI: 10.3390/microorganisms8010136
|View full text |Cite
|
Sign up to set email alerts
|

Waddlia chondrophila and Male Infertility

Abstract: Waddlia chondrophila, a Chlamydia-like bacterium, has been previously associated with adverse pregnancy outcomes. Analogously to Chlamydia trachomatis, W. chondrophila also negatively impacts human semen and may be a source of impaired male fertility. In this study, we analyzed W. chondrophila seroprevalence in a population of male patients of infertile couples and the impact of past exposition to this bacterium on semen parameters. Our results show a surprisingly high seroprevalence of W. chondrophila, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Studies in men have found associations between microbial taxa and sperm concentration, motility, and quality. Some microbes are associated with a reduction in sperm quality, whereas others are associated with higher quality sperm, suggesting that certain microbes may be indicators of sperm quality [ 32 , 66 ]. A recent study conducted in peccaries (Pecari tajacu) also highlighted the relation between preputial microbiome and semen quality [ 67 ].…”
Section: Links Between Microbiomes Life Stage and Reproductive Status In Males And Femalesmentioning
confidence: 99%
“…Studies in men have found associations between microbial taxa and sperm concentration, motility, and quality. Some microbes are associated with a reduction in sperm quality, whereas others are associated with higher quality sperm, suggesting that certain microbes may be indicators of sperm quality [ 32 , 66 ]. A recent study conducted in peccaries (Pecari tajacu) also highlighted the relation between preputial microbiome and semen quality [ 67 ].…”
Section: Links Between Microbiomes Life Stage and Reproductive Status In Males And Femalesmentioning
confidence: 99%
“…Viability and mitochondrial membrane potential of human spermatozoa were reduced when challenged and infected with W. chondrophila [ 14 ]. Studies also showed a high seroprevalence of W. chondrophila in men of infertile couples although the organism was seemed to be absent in semen which suggested a possible hypothesis that the negative effect on male infertility may be observed only during an ongoing infection [ 15 ]. The organism was shown to replicate in several human cell lines including fibroblasts, A549 pneumocytes, peripheral blood mononuclear cells, and in Ishikawa endometrial cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these diseases are incited by uncommon microorganisms. For example Waddlia chondrophila a chlamydia-like bacterium has been reported to impact negatively on the semen, sometimes when another disease may be progressing in the case (Baud et al, 2020) Phytochemicals are compounds derived from plants through diverse forms of release, mostly by extraction (Zhang et al, 2015). They are attractive and strategic products of bioprospecting with application in medicine (Vishnuprasad & Unnikannan, 2017), food safety, food processing, production and storage (Velazhahan & others, 2017).…”
Section: Introductionmentioning
confidence: 99%